Political Strategies of Female Politicians in Shaping the Image of Female Leaders in the Local Political Arena: A Study of Gina Belanza Mulia, Member of the Bondowoso Regency Regional People’s Representative Council for the 2024–2029 Period - Heniwati Heniwati; Puteri Raudatul Jannah; Heny Fajriyah Novianti; Yuda Yuliyanto (Journal of Political and Governance Studies, 2026)
Background This study aims to analyze the political strategies employed by female politicians in shaping leadership images within local politics, with a case study of Gina Belanza Mulia in the Regional House of Representatives (DPRD) of Bondowoso Regency for the 2024–2029 period. Methods Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation, and analyzed using reduction, presentation, and verification with source triangulation. Results The findings reveal that Gina Belanza integrates her vision, Gerakan Berani Maju (Movement to Dare Progress), with socially grounded communication, strategic use of digital media, and cultural relations with religious and local leaders. Offensive strategies are reflected in her image as a progressive and religious young leader, while defensive strategies are evident in consolidating support through party structures and local networks to overcome patriarchal and cultural barriers. Conclusion This study concludes that Gina Belanza’s political strategies and personal branding significantly strengthen women’s political representation in Bondowoso, marking a shift from descriptive to substantive representation. The implications suggest that digital communication combined with cultural adaptation can serve as a model for female politicians in local contexts to enhance leadership legitimacy and contribute to gender-based democratic transformation.